Pendampingan Pembibitan Jambu Mete Unggul Lokal di Klaster Mete Wonogiri - Bambang Pujiasmanto; Trijono Djoko Sulistyo; Supriyono Supriyono; Eko Murniyanto (Universitas Sebelas Maret, 2022)
Assistance for Local Superior Cashew Seedlings in the Wonogiri Cashew Cluster. The innovation adoption process can be accelerated if the communicant makes innovations. Experience in innovating with guidance increases absorption, strengthens expert power, and eventually adopts faster, especially if the communicant is freed to express himself. Referring to this process, mentoring through technical guidance activities and performance on grafting seed innovation of chasew plant is suspected of adopting the provision of seeds on a self-supporting basis. This activity aimed to provide cashew seeds to expand the cashew plant area as well as rejuvenate old cashew plants in order to maintain production. The mentoring method is carried out in stages, namely calculating the need for seeds, demonstrating of chasew plant grafting nursery, the performance of the chasew plant grafting nursery, and building a market network. Instructions and materials and tools were provided by the mentor. The results of the mentoring showed that the productivity of participants in grafting cashew seeds increased to 48-98 seeds per day. Based on the calculations, it was found that for an area of 35.4 Ha, 6,730 seedlings were needed, or the equivalent of 190 seedlings/Ha. Calculation of business analysis obtained that the income received by farmers every month reaches Rp. 8,790,000,-. Cashew seedling mentoring activities are able to increase the productivity and income of cashew farmers.